Annual Address to the Board of Governors, September 27, 1965 - Woods, George D. (World Bank, Washington, DC, 2019)
George D. Woods, President of the World Bank and its affiliates, spoke about raising living standards; the World Bank Group funds to financing development; efforts to encourage private international investment, and two special projects, namely, amendment of the Bank and International Finance Corporation (IFC) charters and convention on the settlement of investment disputes; and two initiatives of the Bank, namely, a study, organized jointly by the International Coffee Organization, Food and Agriculture Organization (FAO), and the Bank, and proposal put forward by the United Kingdom and Swedish delegations at the 1964 United Nations conference on trade and development.